Breast calcifications: Which are malignant? - Malai Muttarak (2018)
Most calcifications depicted on mammograms are benign. However, calcifications are important because they can be the first and earliest sign of malignancy. For detection and analysis of microcalcifications, high-quality images and magnification views are required. The American College of Radiology (ACR) Breast Imaging Reporting and Data System (BI-RADS) classifies calcif ications on mammograms into three categories: typical benign, intermediate concern and higher probability of malignancy, according to types and distribution of calcifications. Benign calcifications are typically larger, coarser, round with smooth margins and have a scattered or diffuse distribution. Malignant calcifications are typically grouped or clustered, pleomorphic, fine and with linear branching. It is important for radiologists to detect, evaluate, classify and provide appropriate recommendations for calcifications perceived on mammograms to provide proper management.